FOMO DAN KRISIS EKSISTENSI: MEMBONGKAR KECEMASAN MODERN MELALUI LENSA EKSISTENSIALISME DAN SOLUSI AL-QUR’AN - Salamah, Ika Hilmiatus; Supena, Ilyas (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study emphasises the existence of an existential crisis among the public, especially social media users, which is commonly referred to as Fear of Missing Out (FOMO). This research aims to uncover the Fear of Missing Out, which is a modern anxiety with the philosophy of existentialism and the solution of the Qur'an. The method used is library research with a descriptive-analytical approach and the use of thematic verses. There are three findings of this study: the first is the Philosophical View of Existentialism Towards the Fear of Missing Out, the second, the Correlation of Fear of Missing Out with the Concept of Existential Anxiety in Islam and the third is the Qur'anic Solution to the Fear of Missing Out. When viewed from the perspective of existentialism, Fear of Missing Out is a form of awareness of self-freedom, accepting anxiety and uncertainty as a natural part of existence. Meanwhile, the solution of the Qur'an is to always behave with tawakkal and qana'ah. With tawakkal, people will realise that Allah is Omniscient and by giving thanks and supplicating Allah, they can avoid feelings of envy that destroy peace of mind.